Dehydroepiandrosterone administration before IVF in poor responders: a prospective cohort study. Issue 2 (February 2015) - Vlahos, Nikos; Papalouka, Maria; Triantafyllidou, Olga; Vlachos, Athanasios; Vakas, Panagiotis; Grimbizis, Gregory; Creatsas, George; Zikopoulos, Konstantinos
Abstract The use of dehydroepiandrosterone (DHEA) may improve ovarian stimulation outcomes in women of advanced reproductive age and could reduce embryo aneuploidy. In this prospective study, 48 women diagnosed with poor ovarian response received DHEA supplementation for at least 12 weeks. These women were compared with a group of poor responders (n = 113) who did not receive supplementation. During the study period, patients taking day 2 FSH and oestradiol were measured monthly before and after treatment. Stimulation characteristics, stimulation outcome and clinical outcome (clinical pregnancy and live birth rates) were reported. Evaluation of anti-Müllerian hormone (AMH) was carried out before initiation of treatment and immediately before the subsequent stimulation. Supplementation with DHEA for at least 12 weeks resulted in a modest, but statistically significant, increase in AMH levels and decrease in baseline FSH (P < 0.001 and P = 0.007, respectively). Administration of DHEA had no effect on any of the stimulation parameters nor was there any difference in clinical pregnancy rates and live birth rates between the two groups. Supplementation with DHEA significantly affects women with poor prognosis undergoing ovarian stimulation for IVF. Patients should be counselled about the uncertain effectiveness, potential side-effects and cost of this treatment.